THE INFLUENCE OF FOREIGN EXCHANGE RESERVES, EXPORTS, IMPORTS, INFLATION, GROSS DOMESTIC PRODUCT (GDP) AND MONEY SUPPLY ON EXCHANGE RATES IN ASEAN COUNTRIES - Rezeta, Frila; Soelistyo, Aris; Fuddin, Muhammad Khoirul (Jurnal Apresiasi Ekonomi, 2024)
The exchange rate for each country is very important because the stronger the exchange rate of a currency in a country, it indicates that the level of the economy in the country concerned has increased and is good. how and whether foreign exchange reserves, exports, imports, inflation, GDP, and money supply can affect the exchange rate in 11 ASEAN countries. This study aims to analyze how the effect of foreign exchange reserves, exports, imports and also inflation on exchange rates in the country, the results of this study are generated from processing using panel data with 20 years of data from 2003-2022 and 11 ASEAN countries. In this study, the method we used to support the creation of this research is a quantitative method with panel data and multiple linear regression approaches where in this study using data - data that has been hung with panel data models used to support the results of this study. The results of this study indicate that the best model is the Fixet Effect estimation and the test results of the foreign exchange reserve variable (X1) has a negative insignificant effect, the export variable (X2) is negative significant, the import variable (X3) is positive significant, the inflation variable (X4) is insignificant, GDP (X5) is negative significant and the money supply variable (X6) has a significant effect on exchange rates in ASEAN countries.Keywords: Foreign exchange reserves, exports, imports, exchange rate, GDP, money supply.